Renin-Angiotensin System Blockade is Associated with Exercise Capacity, Sympathetic Activity and Endothelial Function in Patients with Chronic Kidney Disease - Jin Hee Jeong; Justin D. Sprick; Dana DaCosta; Arshed A. Quyyumi; Jeanie Park (Karger Publishers, 2021)
Background: Chronic kidney disease (CKD) patients have exercise intolerance and exaggerated blood pressure reactivity during exercise that are mediated by sympathetic nervous system (SNS) overactivation and decreased nitric oxide (NO) bioavailability. Activation of the renin-angiotensin system (RAS) increases SNS activation and reduces NO synthesis, and prior studies suggest that RAS blockade attenuates declines in physical function. We hypothesized that RAS inhibitor (RASi) use is associated with higher exercise capacity mediated by decreased SNS activity and increased NO-dependent endothelial function in CKD. Method: In 35 CKD patients (57 ± 7 years) and 20 controls (CON, 53 ± 8 years), we measured exercise capacity (VO2peak), muscle sympathetic nervous activity (MSNA) and flow-mediated dilation (FMD) for NO-dependent endothelial function. Results: CKD patients treated with RASi (CKD+RASi, n=25) had greater VO2 peak compared to CKD patients not treated with RASi (CKD no RASi, n=10), but lower VO2 peak compared to CON (23.3 ± 5.8 vs.16.4 ± 2.9, p=0.007; vs.30.0 ± 7.7, p=0.016 ml/min/kg respectively). CKD+RASi had lower resting MSNA and greater FMD compared to CKD no RASi. Compared to CON, CKD+RASi had similar MSNA but lower FMD. VO2 peak was positively associated with FMD (r=0.417, p=0.038) and was predicted by the combination of FMD and RASi status (r2 =0.344, p=0.01) and MSNA and RASi status (r2 =0.575, p=0.040) in CKD patients. Conclusion: In summary, CKD patients on RASi have higher exercise capacity compared to those not on RASi. Higher exercise capacity in RASi-treated group was associated with lower resting SNS activity and higher NO-dependent vascular endothelial function.